Identification of the Impact of Online Game Addiction - Syahrul, Fitriani F; Wiharjo, Suyadi Murdi; Bahri, Efri Syamsul (Journal of Psychology and Sustainable Education, 2024)
Online Game Addiction in Indonesia reaches 14%, Asia's highest category. This study aims to identify the impact of online game addiction in Indonesia. This research uses a qualitative, descriptive approach and a literature study. The research data comes from journal articles related to online game addiction. The study results show that online game addiction negatively impacts nine dimensions: moral, educational, health, psychological, social, physical, financial, character, and spiritual. Therefore, government agencies must present policies to protect the younger generation from online game addiction. In addition, families are needed to prevent and reduce the impact of addiction to online games.